Influence of Fencing Training (Technical and Tactical) on Selected Features of Shape of the Spine and Pelvis Under Load - Alicja Kaiser; Marek Sokołowski; Mirosław Mrozkowiak (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
The aim of the research was to assess influence of a 90-minute specialist fencing training on selected features of the spine and pelvis under a vertical load in a group of young competitors. The research was carried out in 2015 among 23 fencers (mean ± SD, age: 16 ±1.20 years; body height: 168.4 ±4.68 cm; body weight: 54.7 ±8.26 kg). The method involved measurement of thirty features, describing spatially pelvis and physiological spinal curvature under a vertical load, constituting 1/3 of the body weight before and after specialist training. Statistically significant disturbances in vertically overstretched posture occurred after the training among examined boys within the following features: increase in length of left side scoliosis, progression of lumbar lordosis and lumbosacral spine, increase of the trunk extension angle and shoulder asymmetry. Among examined girls statistically significant changes occurred only within pelvis area: increase of left pelvic tilt in the coronal plane, decrease of right pelvic tilt in the horizontal plane. Adjustment in deficiencies within hip joints movement, increase pelvis and lower limbs muscle strength in girls’ training is necessary. What is recommended for all competitors is prophylaxis of the spinal pain syndrome and expanding endurance shaping exercises during a training unit.